Meningkatkan Kreativitas Anak Melalui Alat Permainan Edukatif Pada Kelompok B Di TK Buah Hati Nupabomba - Mariam, Came (Bungamputi, 2014)
ABSTRACT The problem in this study is whether creativity can be enhanced through educational toys in TK group B Nupabomba Buah Hati? The experiment was conducted in a Child Tk Nupabomba, involving 15 children consisted of 6 boys and 9 girls enrolled in the academic year 2012/2013 . The design of this research study Kemmis and Mc. Taggart consisting of two cycles. Where on each cycle of meetings held three times in the classroom and each cycle consists of four stages: planning, implementation, observation , and reflection. Data were collected through observation techniques, assignments, and then analyzed by descriptive documentation of qualitative and quantitative data. Data collected prior to the action being assessed in the aspect of courage Verry Good 6.66%, Excellent 6.66%, Enough 6.66%, and Less 80%, then the curious aspects of the category Verry Good of 6.66%, 13.33% Excellent, Enough 6.66%, Less 73.33%, and the child's ability to produce unique works of Verry Good category 6.66%, Excellent 6.66%, Enough 13.33%, and Less 73.33%. After the action is taken, the results of this study it can be concluded that through educational toys can enhance the creativity of children, there is an increased ability proved from the first cycle to the second cycle in the aspect of courage is excellent and good categories from 26.66% to 73.32% (46,66%), aspect ungin know very well and good categories from 26.66% to 73.32% (46.66%), producing unique works excellent and good categories from 26.66% to 66.66% (40%). In general, an increase in the average 44.44 % of cycle one to cycle two, although there are still children who have not increased their creativity but only about 13.33 % of the aspects of each category observed with less. Â Keyword: Childresnâ€™s Creativity, Educational Gaming Device